Pendampingan Pengembangan Modul Ajar Matematika Berbasis Etnomatematika di SMA: Evaluasi dan Penyempurnaan - Bela, Maria Editha; Wewe, Melkior; Wangge, Maria Carmelita Tali; Hari, Christina Lusiana; Lola, Teofania Kristina; Leoni Jari, Walburga Laong; Lewa, Yusta Selvianjeli (Abdimas Mandalika, 2025)
Abstract:  The purpose of this community service activity is to improve the ability of mathematics teachers in developing ethnomathematics-based mathematics teaching modules by providing mentoring to teachers in developing teaching modules. This activity was carried out at Citra Bakti High School with 10 Mathematics Teachers who are members of the MGMP in Golewa District. The approach used in this activity was Interviews, Face-to-face, and direct mentoring which was carried out in July 2025. The methods used in this activity included evaluation workshops and reflective discussions with teachers and students to obtain constructive feedback. Evaluation was carried out based on aspects of material feasibility, learning effectiveness, and integration of local cultural values in mathematical concepts. The data collection instrument used in this Community Service activity was a participant response questionnaire with a Likert scale category on a 4-point scale, namely very good, good, less good, and very less good. Data were analyzed referring to indicators, namely participant satisfaction, material relevance, and usefulness. The results of the mentoring activity showed that the satisfaction aspect showed a very good response, the relevance of the material was very good, and the usefulness of the material was very good.Abstrak: Tujuan kegiatan pengabdian ini adalah untuk meningkatkan kemampuan guru matematika dalam mengembangkan modul ajar matematika berbasis etnomatematika dengan cara memberikan pendampingan terhadap guru dalam mengembangkan modul ajar. Kegiatan ini dilaksanakan di SMA Citra Bakti dengan 8 Guru Matematika yang tergabung dalam MGMP di Kecamatan Golewa. Pendekatan yang digunakan dalam kegiatan ini adalah Wawancara, Tatap muka, dan pendampingan langsung yang dilaksanakan pada bulan Juli 2025. Metode yang digunakan dalam kegiatan ini mencakup workshop evaluasi dan diskusi reflektif bersama guru dan siswa untuk mendapatkan umpan balik yang konstruktif. Evaluasi dilakukan berdasarkan aspek kelayakan materi, efektivitas pembelajaran, dan keterpaduan nilai budaya lokal dalam konsep matematika.Instrumen pengumpulan data yang digunakan dalam kegiatan Pengabdian kepada Masyarakat ini adalah angket respon peserta dengan kategori skala likert pada skala 4 poin yaitu sangat baik, baik, kurang baik, dan sangat kurang baik. Data dianalisis mengacu pada indikator yaitu kepuasan peserta, relevansi materi, dan kebermanfaatan. Hasil kegiatan pendampingan menunjukkan aspek kepuasan menunjukkan respon sangat baik, relevansi materi sangat baik, dan kebermanfaatan materi sangat baik.